Kajian Hukum Islam Tentang Wasiat Wajibah Kepada Ahli Waris Beda Agama - Safira Rahmi Khouw; La Ode Angga; Sabri Fataruba (Faculty of Law, Universitas Pattimura, 2022)
Introduction: In Islamic Inheritance Law, the person who is entitled to receive inheritance from the heir is also a Muslim, so it is very difficult for people who are not Muslim to be able to inherit even if the heir and heirs have a relationship as husband and wife, therefore it needs a breakthrough from the judge.Purposes of the Research: To find out and analyze Mandatory Wills according to Islamic Law and Supreme Court Decision Number 16K/AG/2010 relating to Mandatory Wills to non-Muslims. Methods of the Research: The research method used is normative legal research, all legal materials, both primary, secondary, and tertiary are collected and compiled qualitatively.Results of the Research: The results of this study indicate that the provisions of the mandatory will according to the Compilation of Islamic Law also apply to adoptive parents and adopted children, as regulated in Article 209 of the Compilation of Islamic Law, namely: a. the inheritance of the adopted child is divided according to Articles 176 to 193 of the KHI, while the adoptive parents who do not receive a will are given a mandatory will as much as 1/3 of the inheritance of their adopted child; and b. against adopted children who do not receive a mandatory will as much as 1/3 of the inheritance of their adoptive parents. Furthermore, although in Islamic law a wife who is a non-Muslim religion is not entitled to inherit property from her Muslim husband, but on the basis of the judge's considerations using the results of ijtihad from fiqh experts who expand the provisions regarding mandatory wills which only apply to relatives who are not married, obtaining inheritance from the heir to apply also to a wife who is a religion other than Islam is the most likely way as a middle and alternative way to be taken in order to create justice.